Images and Objects of Russia's War against Ukraine (transcript Verlag, 2025)
Russia’s full-scale invasion of Ukraine in February 2022 has destroyed lives, communities, and cities. From the start, images of this war spread across various media platforms. Paintings, photographs, drone footage, TikToks, and Instagram posts shaped how the war is experienced, represented, and archived. In this multidisciplinary volume, artists, scholars, and writers explore how art, media, infrastructures, and material culture respond to and contest the Russo-Ukrainian War.